The problematic politics of China's economic reform plans - Guy De Jonquières (European Centre for International Political Economy (ECIPE), 2014)
China is in a race against time to re-engineer its faltering economic model, famously described by Wen Jiabao, its last prime minister, as "unsustainable, uncoordinated, unbalanced, and unstable". Against a background of soaring debt levels, proliferating asset bubbles and chronic excess capacity in many sectors, Xi Jinping, China's President, has announced a programme of sweeping, market-oriented, structural reforms intended to "re-balance" its economy and lay the foundations for the country's future growth. Since taking office in 2012, Mr Xi has rapidly accumulated massive personal power and tightened his grip on the ruling Communist Party, while instituting one of the most ferocious crackdowns on corruption in China's history. By establishing an unchallenged hold over the Party's machinery and national decision-making, he has put himself in an exceptionally strong position to ram through much-needed changes in policy and bulldoze obstacles to the planned reforms. However, as Guy de Jonquières argues in this policy brief, tightening political control while seeking simultaneously to free up the economy by expanding the role of markets has created a fundamental paradox. To be effective, many of China's reform proposals will entail less - not more - state intervention and reduced politicisation of the legal system and other economically important institutions. Yet the core purpose, indeed, the raison d'être, of the Communist Party is the right to exercise unfettered power over every aspect of Chinese society - and that right is unlikely to be surrendered willingly. How the paradox will be resolved is still far from clear.
Keywords: 330; Volkswirtschaftsplan; China